HIPCAR - electronic transactions : model policy guidelines & legislative texts (ITU Place des NationsCH, 2013)
Provides for the equivalence of paper and electronic documents and contracts and the foundation of undertaking commerce in cyber-space.
HIPCAR's objective is to assist CARIFORUM Countries in the Caribbean to harmonise their information and communication technology (ICT) policies, legislation and regulatory procedures.\n \n